Exploring the Impact of Twin-Block Appliances on Sleep-Disordered Breathing and Sleep Quality in Children: A Scoping Review - Intan Winari; Meirina Gartika (International Journal Labs, 2026)
Sleep-disordered breathing (SDB), including conditions such as obstructive sleep apnea (OSA), poses a serious concern in children due to its negative effects on cognition, behavior, and overall well-being. One of the underlying causes of SDB is mandibular skeletal deficiency, which is frequently observed in Class II malocclusion. The Twin-Block appliance, a functional orthodontic device, has been explored for its ability to advance the mandible and potentially improve airway patency and sleep-related physiological parameters. This scoping review aimed to explore and summarize the breadth of existing evidence concerning the influence of Twin-Block treatment on pediatric SDB and sleep quality. A comprehensive search, guided by the participants, interventions, comparisons, outcomes, and study design (PICOS) framework, was conducted across PubMed, Scopus, and ScienceDirect for studies published between 2015 and 2025. Abstracts, eligible full texts, and reference lists were screened, and all reported primary and non-primary outcomes, as well as methods of measurement, were recorded. Eligible studies included clinical and observational research assessing outcomes such as the apnea-hypopnea index (AHI), blood oxygen saturation, airway morphology, and aspects of sleep architecture. The review process followed Joanna Briggs Institute (JBI) methodological guidance for scoping reviews. Thirteen studies met the inclusion criteria, most of which demonstrated positive changes following Twin-Block intervention, including reduced AHI, improved oxygen saturation, enlarged upper airway dimensions, and enhanced sleep quality. However, discrepancies in research designs, intervention protocols, and measurement tools contributed to substantial variability across studies. Twin-Block therapy may provide a beneficial complementary approach to managing SDB in children, especially those with mandibular deficiencies. Nonetheless, more rigorous and standardized studies are necessary to confirm its effectiveness and support its broader application in clinical practice.